STYLISTIC ANALYSIS OF IMAGERY IN THE POETRY COLLECTION OF SLEEPING SONGS BY AMA GASPAR - mutia aksari; Erni (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to describe the type, distribution, and tendency of the use of imagery in the collection of poems Lagu Sleep by Ama Gaspar as a representation of the aesthetic strategy of contemporary Indonesian poetry. The focus of the research is directed at six types of imagery, namely visual, hearing, smell, taste, tactile and movement images, which play an important role in building the reader’s aesthetic meaning and experience. This study uses a descriptive qualitative approach with a type of literature research. The data source is in the form of a collection of poems Sleeping Song by Ama Gaspar which contains 82 poems, with 52 poems selected as research data based on the completeness and clarity of the imagery elements. Data in the form of words, phrases, and expressions were analyzed using content analysis techniques through the stages of identification, classification, and interpretation of images. The validity of the data is maintained through repeated reading and checking the consistency of classification by peer researchers. The results of the study showed that 151 imaging data were found spread across six types of images, with details: 50 data visual images, 35 data auditory images, 32 motion images, 18 sensory images, 10 sensory images, and 6 sensory images. Visual imagery is the most dominant type, characterized by visual depictions of objects, light, colors, and spaces that function to concretize the inner experience of the lyrical figure. Auditory and motion imagery support mood dynamics and emotional conflict, while other imagery enriches layers of affective and symbolic meaning. The discussion suggests that the dominance of visual imagery reflects the tendency of visuality in contemporary poetry, while other variations of imagery show the use of human sensory experience as the primary poetic strategy. The novelty of this research lies in the comprehensive mapping of all types of imagery and its tendency to dominate contemporary poetry works that are relatively new and have not been studied stylistically, especially the work of Ama Gaspar. These findings contribute to the development of the study of the stylistics of Indonesian poetry and can be used as a reference in literary learning.